Analysis of the triplet exciton transfer mechanism at the heterojunctions of organic light-emitting diodes. (9th June 2020) - Huang, Jun-Yu; Wang, Mei-Tan; Chen, Guan-Yu; Li, Jung-Yu; Chen, Shih-Pu; Lee, Jiun-Haw; Chiu, Tien-Lung; Wu, Yuh-Renn
Abstract: In this study, a model was proposed to analyze the triplet exciton transfer at the heterojunction interface and emission efficiency. The experimental results obtained for four devices with and without exciton blocking layers (EBLs) were analyzed. Although the incorporation of an EBL improved the peak external quantum efficiency (EQE) due to exciton blocking, the efficiency droop behavior became stronger, and the EQE was worse than that of the reference device without an EBL at current densities over 5 mA cm −2 . To understand the physical mechanism underlying this observation, a new carrier transport simulation program was developed. This program considered a multi-Gaussian shape density of states, field-dependent mobility, exciton diffusion, triplet–triplet annihilation, triplet–polaron quenching and triplet exciton transfer at the interface. The simulation results showed that although the excitons were blocked at low current density when an EBL was used, the large exciton density generated at the interface and strong annihilation behavior resulted in a strong droop behavior. The other key factor was that the EBL limits hole injection; this resulted in stronger overflow at high current density, which reduced the efficiency and exhibited such switching behavior.